Evaluation of Community Processes and Analysis of Inter-Organizational Networks: Improving the Effectiveness of Community Intervention - Ramos Vidal, Ignacio; Holgado, Daniel; Maya Jariego, Isidro; Palacio, Jorge E. (Pensando Psicología, 2014)
The aim of this article is to investigate the connection that exists between the psychological sense of community, community participation, and the analysis of organizational networks, examining the influence of these approaches on individual, organizational and community levels of analysis. Accordingly, we review the literature from each of these three perspectives, then analyze the way they are linked with different levels of analysis. Finally, we offer some suggestions as to how the application of a multi-level ecological approach could improve the effectiveness of community intervention.